The Effect of Corporate Political Engagement on Environment, Social, & Governance (ESG) Disclosure - Verna Budi Amanda; Ainun Na'Im (Accounting Analysis Journal, 2024)
Purpose : The research investigates the relationship between corporate political engagement and ESG disclosure moderated by the ownership structure and mediated by earnings quality. The sample for this study consists of companies that sponsor, build, and operate steam power plants in Indonesia. Method : Sample consists of 22 companies sponsoring, constructing, and operating steam power plants in Indonesia particularly during the period 2019-2021. In testing for the direct effect, moderation effect, and mediation effect, the researchers use multiple regression analysis, moderated regression analysis, and path analysis. Findings : The results of the statistical test show evidence that corporate political engagement has a negative relationship with ESG disclosure and the ownership structure is capable of weakening the negative relationship between corporate political engagement and ESG disclosure. However, earnings quality is unable to mediate the relationship between corporate political engagement and ESG disclosure. Novelty : The research has several original factors. First, this research utilizes ownership structure as a moderation variable and earnings quality as a mediation variable. Second, this research analyzes the relationship between corporate political engagement and all the ESG components, aiming for more comprehensive results compared to previous studies.